THE ROLE OF EDUCATION IN HUMAN DEVELOPMENT IN DISTRICTS / CITIES OF RIAU PROVINCE - Aswanto Aswanto; Emkhad Arif; Mhd Suleman Hsb (Journal of Applied Economics in Developing Countries, 2024)
The purpose of this study is to see the data and then analyze how big the role of education is with its indicator Average Length of Schooling (RLS) in improving human development with its indicator Human Development Index (HDI) in the Districts/City of Riau Province. By using data sourced from the BPS of Riau Province, namely Secondary data. And using a descriptive analysis method then strengthened by simple regression testing using panel data, using the Eviews 13 Statistics application. So based on the results of the study it can be concluded that the role of Education plays a very important role in Human Development in the Districts/City of Riau Province. Proven in partial testing, education (RLS) has a positive and significant influence on human development (HDI) which is indicated by a Prob value of 0.0000 which is less than 0.05. Meanwhile, the magnitude of the influence can be seen from the value of the calculation results obtained by the Determination Coefficient (Adjusted R2) in this study, which is 93.97%. Of course, in this study there are still limitations in problems that are not discussed thoroughly. However, the results of this study can be a reference in government policy to increase the role of education in human development in Riau Province.